Analysis of several factors that affect auditor job statistics and their relationship with auditor turnover (comparison of foreign affiliated heads of South Jakarta and non-foreign affiliated heads) - Dyah Ayu Citra Fitria (Indonesia Auditing Research Journal, 2022)
The purposes of this research are examining the factors that influence auditor's job statistics and the effects of job statistics to auditor's turnover. In this research, job statistics are measured by a descriptive job index such as work itself, pay, promotion, boss, and co-worker. The data were collected by distributing questionnaires to auditors who work on the public accounting in South Jakarta. The total sample is 80 which consists of 50 auditors from affiliated accounting firms and 30 auditors from non-affiliated accounting firms. The data were analyzed with two models of regression (multiple regression) The results showed that in non-affiliation accounting firms, only mentoring and motivation had positive significant effects on auditor's job statistics, while in affiliation accounting firms, mentoring, motivation, and hygiene factors had positive significant effects on auditor's statistics. Job satisfaction has a negative significant effect on turnover in two types of accounting firms. If the auditors are satisfied with the work, then their turnover will be low.